ANALISA HUBUNGAN BEBAN PAJAK PENGHASILAN TAHUN SEBELUMNYA TERHADAP AKTIVITAS EARNING MANAGEMENT TAHUN BERJALAN DENGAN MENGGUNAKAN FIRM SIZE DAN LEVERAGE SEBAGAI VARIABLE CONTROL PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI DI INDONESIA - Vanesa Pradipta Candra; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study was intended to test if there was a relation between income tax expense and earning management. The sample used in this study was manufactures listed in Jakarta Stock exchange. The data collected from annual reports of 2010-2015 with the of total 163 firm years. The hypothesis in this study by using tested by using double regression anlaysis. Income tax expense measured by using company’s income tax expense divided by the total of the company’s final assets. Earning management measured by Modified Jones model. This study also used control variables, of firm size and leverage. The study found that firm size variable was prove to have a negative effect on earning management, and income tax expense variable and leverage were prove to have positive affect on earning management. Simultaneously, last year’s income tax expense, firm size and leverage had effects on earning management.